The influence of post-cracked exposure period on some physical properties of palm kernel shells (2000)
A series of experiments were conducted to measure the influence of the duration of exposure to inclement weather after cracking on the bulk density, solid or true density, porosity, and water absorption characteristics of palm kernel shells (PKS). The results showed that the bulk and true densities decreased respectively from 0.60g/cm3 and 1.37g/cm3 for freshly cracked shells to 0.53g/cm3 and 1.25g/cm3 for shells that have been exposed to inclement weather for over ten years after cracking. The porosity and ability to hold moisture increased with the duration of exposure. These experimental observations are attributable to the organic nature of the shells as a result of which there is a gradual biodeterioration especially of the adhering fibers. This reduces the dry matter content and increase the void. Density values obtained are comparable with other materials of construction such as earth and wood which is an indication that PKS has potentials for use as a material for construction. Further work on the mechanical properties of the material is recommended.